How I resist : activism and hope for a new generation - Johnson, Maureen, 1973- (Wednesday Books, 2018)
Presents a collection of essays, interviews, and songs from over twenty-five celebrities, authors, and leading activists on how young people can get started in activism and fighting for their beliefs.